2016
DOI: 10.1002/admi.201600534
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastrong Anchoring on the Periodic Atomic Grooves of Black Phosphorus

Abstract: the range of aligned molecules may be limited to those possessing strong π-π interactions with 2D materials. [19][20][21] In this regard, grooved surfaces can provide a powerful approach, because the anchoring energy and anchoring direction of their patterned surface can be artificially designed by controlling the direction, amplitude, and period of the patterned substrate according to Berreman's theory. [22][23][24] Despite the success achieved with aligning lyotropic chromonic liquid crystals (LC) by introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 43 publications
(94 reference statements)
2
16
0
2
Order By: Relevance
“…Thedegradation caused by air and water in the case of BP has become an issue paralleled only by the concerns of metallic and oxidation debris in the preparation of carbon nanomaterials. [104] requisite to retain the intrinsic material properties of BP and advance its applications. [48,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] Other authors have taken advantage of this stability issue and proposed using BP in humidity sensors (Section 4.3).…”
Section: Chemical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Thedegradation caused by air and water in the case of BP has become an issue paralleled only by the concerns of metallic and oxidation debris in the preparation of carbon nanomaterials. [104] requisite to retain the intrinsic material properties of BP and advance its applications. [48,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] Other authors have taken advantage of this stability issue and proposed using BP in humidity sensors (Section 4.3).…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…[102] Bulk BP appears to be stable over aprolonged period of time under ambient conditions. [104] Kim et al point out that the planar anchoring of the aligned soft materials is fixed in one direction, which the authors attributed to the regular atomic-scale grooves of BP inducing an ultrastrong azimuthal anchoring energy of the soft materials (ca. [17,90,103] It was recently demonstrated that the puckered honeycomb structure of BP enables the controlled alignment of awide range of soft materials,including rodlike molecules and even dendrimers ( Figure 1D).…”
Section: Chemical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[11] As an allotrope of elemental phosphorus,B Ps possess excellent element biocompatibility and degrade to nontoxic phosphite/phosphate ions under physiological conditions. [12] BPs with atomic thickness and a2Dpuckered honeycomb structure [13] provide very high surface-to-volume ratios among various nanomaterials.Furthermore,the periodic atomic grooves on surfaces of BPs provide ideal anchoring sites for proteins [14] and soft linear materials, [15] indicating their potentials in loading and delivery of biomolecules.B Ps-based approaches have thus been employed in numerous biomedical applications. [16] However,t he applications of BPs in cytosolic delivery of bioactive macromolecules have not yet been reported.…”
mentioning
confidence: 99%